The Utilization of Quizizz-Based Educational Games to Enhance the Cognitive Abilities of Children Aged 5–6 at Raudatush Shibyan Kindergarten - Juliani Hidayah; Gunawan Gunawan; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2025)
Quizizz-based educational game media is an innovative learning tool that integrates play with instruction, fostering a more engaging and interactive environment for cognitive development. This study addresses the challenges of low cognitive abilities in problem-solving, logical thinking, and symbolic thinking among children at TK Raudatush Shibyan, which are often attributed to teacher-centered methods and limited digital media integration. Using a quasi-experimental design with a one-group pretest-posttest approach, the study involved 13 children selected through purposive sampling. Cognitive development was assessed using a pictorial instrument aligned with national early childhood education standards. Data were analyzed using non-parametric statistical tests to determine the significance of the intervention. The findings revealed a substantial increase in children's cognitive scores following the intervention. Statistical analysis confirmed a significant difference between pretest and posttest results, with a large effect size indicating that the use of Quizizz had a profound impact on cognitive improvement. In conclusion, Quizizz-based educational games are proven to be an effective and powerful medium for significantly enhancing the cognitive abilities of children aged 5–6 years.